Identificação do grau de sensitização de uma liga de alumínio-magnésio pelos métodos NAMLT e DL-EPR - Coelho, Arthur César Miná Albuquerque (2018)
Aluminum-magnesium alloys (Al-Mg) are used in many industrial sectors and are widespread in the naval industry. However, magnesium contents above 3%w/w favor the sensitization of these alloys by the precipitation of a phase, called β (Mg 2 Al 3 ), which is deleterious to the property of corrosion resistance. Cracking caused by the sensitization process causes damage to vessels and damages the shipbuilding industry. The objective of this work was to: i) calculate the degree of sensitization (DoS) in different aging conditions through Nitric Acid Mass Loss Test (NAMLT); ii) verify the applicability of Electrochemical Potentiokinetic Reactivation of Double Loop (DL-EPR) in Al-Mg alloys, as well as the calculation of DoS with this technique; and iii) analyze whether cold deformations in Al-Mg alloys interfere with DoS. For the first objective, the samples were submitted to twenty thermal treatment conditions, according to a factorial scheme of five temperature conditions (50, 100, 175, 350 and 500 °C) and four times (1, 24, 72 and 168 h). For the second objective, six thermal treatments were used, three of which presented sensitized samples according to the previous analysis by the NAMLT technique. The results of the previous mass loss analysis were compared with the results obtained by the DL-EPR technique, with the DoS calculated by the ratio between cathodic and anode current peaks (Ir/Ia). The third and the last objective was to use cold rolled samples and samples annealed at 500 °C for 1 h, sensitizing them under two conditions: 175 °C for 1 and 7 days. The experiments showed that at a temperature of 175 °C, regardless of the aging time, and at 100 °C, aged for 168 h, there was a sensitization of the AA 5086 alloy (AlMg4), according to the NAMLT assay, aging at 175 °C by 168 h was a more critical condition. The DL-EPR assays to quantify the DoS in aluminum alloys were shown to be applicable and confirmed by the Ir/Ia ratio the results obtained by the NAMLT technique. Plastic deformations showed to have influence on the increase of the DoS, so that the laminated samples obtained greater mass loss and higher Ir/Ia ratio. The applicability of the DL-EPR technique was also effective in samples with plastic deformations.